Unfavorable Associations Between Serum Trimethylamine N-Oxide and L-Carnitine Levels With Components of Metabolic Syndrome in the Newfoundland Population - Gao, Xiang; Tian, Yuan; Randell, Edward; Zhou, Haicheng; Sun, Guang (Frontiers in Endocrinology, 2019)
Background: We aimed to study the relationships between serum Trimethylamine N-oxide (TMAO) and L-carnitine levels with metabolic syndrome profiles, including obesity, blood pressure, serum lipids, serum glucose and insulin resistance (IR)-related index in humans. Methods: Cross-sectional study was performed in 1081 subjects from the CODING study in Newfoundland. Serum TMAO and L-carnitine levels were quantified by LC-MS/MS. Metabolic markers were measured in all subjects using fasting blood samples. Partial correlation and linear regression analysis was employed after systematicly controlling the major confounding factors, such as age, gender, calorie intake and physical activity level. Results: Serum L-carnitine level was positively correlated with serum triglyceride (TG), serum insulin, IR in males with normal fasting glucose (p<0.05 for all) and positively correlated with only serum TG (p<0.05) in those with hyperglycemia. In females, significant positive correlations were identified between serum L-carnitine level with obesity, serum total cholesterol, glucose, insulin, and IR in those with normal fasting glucose level (p<0.05 for all), while none was found in those with hyperglycemia. Serum TMAO level was only identified to be positively correlated with serum insulin level and IR in hyperglycemic males (p<0.05 for all). Conclusions: Serum L-carnitine level was significantly associated with an unfavorable MS profile mainly in subjects with normal serum glucose level, while serum TMAO level was associated a unfavorable MS profile in subjects with hyperglycemia. The gender difference warrants further investigations.